Maize Price Differences and Evidence of Spatial Integration in Malawi: The case of selected markets - Nyongo, Lovemore (International Food Policy Research Institute, 2014)
This study tests the long-run and short-run integration of maize markets in Malawi using the co-integration approach within the Vector Autoregressive modeling framework. The analysis is extended to Wald-F Granger Causality tests to see the direction of causality between maize markets. A total of six maize markets, two from each region, were analyzed. Three are urban markets, while two of the three rural markets are border markets. The study uses monthly maize retail prices for the period January 2000 to May 2008. Study findings show that nine out of the fifteen market pairs are integrated in the long-run, but the degree of short-run market integration is low, implying that the transmission of price information is slow.